IMPLEMENTASI PENGEMBANGAN MODUL AJAR BERBASIS MODEL MERRIL’S PRINCIPLE OF INSTRUCTION MATA PELAJARAN QUR’AN HADIST KELAS VII MATERI RAHMAT ALLAH SWT DI MTS DARUL AMIN PALANGKA RAYA - Devi Barokah; Jasiah Jasiah (Universitas Negeri Surabaya, 2025)
This study developed a teaching module based on Merrill's Principle of Instruction for the seventh grade Qur'an Hadith subject with the material of the Grace of Allah SWT at MTs Darul Amin Palangka Raya. This module is designed to support the implementation of the independent curriculum, which emphasizes flexibility, creativity, and relevance of learning. The research uses the ADDIE development model which includes the analysis stage, at this stage is the initial stage of making observations to be able to know and understand the actual conditions. The design stage, determining the overall content, namely 1) analyzing the content of the teaching module, 2) designing related to the flow or syntax in learning by applying the Merril's Principle Of Instruction model, 3) selecting teaching material competencies, 4) making the linkage of material examples with real life as easy as possible, 5) implementing the teaching module. Stage Development, at this stage is the most important stage which is developing so as to produce a good and appropriate product, namely the development of Merril's-based teaching modules. Implementation Stage, at this stage presents the results of the finished product of the teaching module that has been implemented with the Merril's model. The Evaluation Stage, is the final stage of seeing the suitability of the components that apply to the teaching modules used by teachers.The results showed that the module based on Merrill's Principle Of Instruction, which includes elements of real tasks, activation, demonstration, and application.